Analysis of Influencing Factors on the Variation of Soluble Inorganic Carbon in Reservoirs in Wujiang River Basin - Liu, Qingshan (International Journal of Natural Resources and Environmental Studies, 2024)
Carbon cycle plays a very important role in geochemical biological processes, there are a large number of lost carbon sinks in the process of calculating carbon sinks, and the carbon sinks after river damming are part of the lost carbon sinks, mainly soluble inorganic carbon (DIC). Select the Wujiang River Basin as the study area, with the help of carbon isotope labeling method to express the change law of carbon elements in the reservoir, and analyze the change law of the vertical profile of DIC. It is concluded that the change law of DIC is affected by dam construction, dissolution of carbonate rocks and aquatic organisms.